Steroid induced ocular hypertension following pterygium surgery - Khatri, BK; Ton, H (Health Renaissance, 2012)
Background: Steroid induced glaucoma is an important cause of ocular morbidity and blindness. Objective: To determine the incidence of steroid induced ocular hypertension following pterygium surgery. Methods: A total of 202 eyes of 202 patients with primary pterygium which received steroid eye drops after undergoing surgical excision were selected. Pre-operative and post-operative intra-ocular pressure (IOP) were measured and followed up after 2nd and 6th weeks following surgery. Results: Ocular hypertension developed in 47 (23.27 %) eyes. The IOP returned to normal after two weeks following discontinuation of topical steroid drops (dexamethasone) and initiation of anti-glaucoma medication (Timolol drops 0.5% BD). Conclusion: Nearly one fourth of the patients receiving topical steroid following pterygium surgery presented with ocular hypertension. Measurement of IOP as early as 2 weeks of initiation of steroid drops helps identify steroid induced ocular hypertension. DOI: http://dx.doi.org/10.3126/hren.v10i1.6009 HREN 2012; 10(1): 57-58